Kerjasama Pemerintah Kota Yogyakarta Dengan BAZNAS Kota Yogyakarta - Hibnu Basuki; R. Widodo Triputro (Program Studi Akuntansi IKOPIN, 2022)
The cooperation built by the Yogyakarta City Government with BAZNAS is the capital of the success of regional development. The purpose of this study is to describe how the cooperation between the Yogyakarta City Government and BAZNAS is reviewed based on four aspects of synergy, namely; common perception, coordination, collaboration and harmony. While the problem of supporting factors as well as the main obstacle in this case is about the legal power of zakat management in The Yogyakarta City. The method used in this research is descriptive qualitative empowered by a triangulation technique. The focus is the cooperation between the Yogyakarta City Government and The BAZNAS. In this study, the authors determine the main subject followed by other sources using purposive sampling technique. The result of the research is that the relationship between the Yogyakarta City Government and The BAZNAS from the aspect of equality of perception, coordination, collaboration and harmony is in line with regional development steps. Furthermore, in the context of the legal power of zakat, there is currently a discourse on the formulation of regional regulations with a wider scope on zakat management. in line with the dynamics of regional development development.